PENGOLAHAN SAMPAH ORGANIK PERKOTAAN MENGGUNAKAN LARVA BLACK SOLDIER FLY (Hermetia illucens) - Lena Monita; Surjono Hadi Sutjahjo; Akhmad Arif Amin; Melta Rini Fahmi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
Black soldier fly (BSF) larvae (Hermetia illucens) can be used as insect based municipal organic waste recycling technology. The purpose of this research was to examine the utilization of BSF larvae as bio-processors of organic waste in order to produce compost and nutritious larvae biomass. Larvae feeds as treatments of experiment consist of restaurant organic waste mixed with fish silage 6% as treatment A, restaurant organic waste with dairy blood waste 6% as treatment B, and restaurant organic waste as treatment C. The result of this research showed that the highest larvae growth according to its length, width and body weigth was resulted by treatment B, followed by treatments A and C. Total metamorphic development time from egg to imago was 35 days; comprised of as larvae, prepupa, pupa, and imago for 12-13, 6, 6, and 15 days, respectively. Proximate analysis showed that BSF larvae had protein content 33.31 to 33.88%, and fat content 30.07 to 34.39%. Final solid residues of the three treatments was ranged from 90.3-90.6% after 10-11 days of bio-processing.